Al-Islām fī Indūnīsīyā: Itārujadīd - Subhan, Arief (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
Intellectual Muslims generally began to attain prominence in the early 20th century, in line with the growing modernization of the Islamic world. During this period, the Islamic world faced colonialism and imperialism which had unthought-of of implications for the wider Muslim community. The struggle against colonialism sparked debate about jihad with a more varied and complex meaning. The cultural struggle that took place between Islam and the West gave rise to a